منهج الإصلاح في رسالات الأنبياء لمواجهة الفساد: دراسة قرآنية تحليلية : (The Methodology of Reform in the Missions of the Prophets in Confronting Corruption: A Qur’anic Analytical Study) - زبير سلطان (At-Tajdid - Intellectual Refereed Journal, 2026)
Abstract This study examines the reformative framework embedded in the prophetic messages through an analytical Qur’anic reading that reconstructs the concept of corruption and its various forms as presented in revelation. It highlights the centrality of combating corruption within the prophetic mission, viewing it as a complex deviation affecting creed, values, and social structures. The study addresses a key scholarly problem: the absence of a comprehensive analytical framework that systematically links Qur’anic classifications of corruption with prophetic mechanisms of reform, beyond moralistic discourse or partial historical narration. Methodologically, the research adopts an objective analytical approach to Qur’anic texts and prophetic models, engaging in a critical dialogue with selected contemporary reform approaches that emphasize procedural regulation while neglecting moral conscience. The study concludes that prophetic reform constitutes an integrated project that begins with correcting the creedal foundation and purifying the soul, then progresses toward legal rectification and social activation, offering a normative framework for critically assessing contemporary reform visions without claiming direct practical application to a specific context. Keywords: Combating corruption, divine messages, civilizational reform, prophetic methodology, renewal of religious discourse.